Interlinkages between service quality, customer satisfaction and customer loyalty in Malaysia: a case study of Armed Forces Medical Organizations - Azman Ismail,; Hafizah Omar Zaki,; Ilyani Ranlan Rose, (School of Social, Development and Environmental Studies, Faculty of Social Science and Humanities, Universiti Kebangsaan Malaysia, 2016)
Although conceptually viewed as abstract and elusive service quality is an important ingredient in quality management, marketing and organizational studies as evidenced by the appearance of various models dealing with it. The Parasuraman et al. (1985, 1988, 1991, 1994) SERVQUAL model conceives of effective service quality as comprising five core components: tangibility, reliability, responsiveness, assurance and empathy. This study was conducted to measure the relationship between service quality, customer satisfaction and customers’ loyalty. Selfreport questionnaires were used to collect data from customers who received treatments at the armed forces health organizations in Peninsular Malaysia. The outcomes of SmartPLS path model analysis demonstrated that the ability of organization to appropriately implement tangibility, reliability, responsiveness, assurance and empathy in performing daily job had strongly invoked customer satisfaction, which in turn might lead to enhanced customers’ loyalty. Nevertheless, future research in this field should consider exploring further individual similarities and differences in influencing the implementation of service quality by organizations, other research designs that can better describe the patterns of change and the direction and magnitude of causal relationships amongst variables of interest, the need for more diverse organizations to be involved, other specific technical and environmental qualities as an important link between service quality and many aspects of customer outcomes, and the use of a larger sample sizes.